2004
DOI: 10.1177/0891988704264534
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a 26-Point Telephone Version of the Mini-Mental State Examination

Abstract: The objective of this study was to assess the convergent validity of a 26-point Telephone Mini-Mental State Examination (MMSE) in a longitudinal cohort of 46 Alzheimer's disease (AD) patients. Paired in-person and telephone MMSE observations were collected within 35 days of each other. The setting was the Stanford/VA Alzheimer's Center in Palo Alto, California, and patients' residences. The 30-point Folstein MMSE was administered in-person, and a 26-point telephone version of the MMSE, adapted from the Adult L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
194
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(206 citation statements)
references
References 11 publications
1
194
0
Order By: Relevance
“…In this prior publication, EDEN trial survivors reported physical function lower than population norms (mean values of 62 and 67% of age-and sex-matched norms for SF-36 Physical Function domain at 6 and 12 mo), similar to 6MWT performance measured in the present study (mean percent predicted values of 64 and 66%, respectively). Using the telephone version of the Mini Mental State Exam (a global cognitive screening tool) (53), the prior publication demonstrated that 25 and 21% of EDEN survivors had cognitive impairment at 6 and 12 months, respectively, compared with 36 and 25% in this study that used a more sensitive and comprehensive battery of performancebased cognitive tests. Similarly, initial trophic feeding versus full enteral feeding did not affect any of the patient-reported outcomes (2).…”
Section: Discussionmentioning
confidence: 99%
“…In this prior publication, EDEN trial survivors reported physical function lower than population norms (mean values of 62 and 67% of age-and sex-matched norms for SF-36 Physical Function domain at 6 and 12 mo), similar to 6MWT performance measured in the present study (mean percent predicted values of 64 and 66%, respectively). Using the telephone version of the Mini Mental State Exam (a global cognitive screening tool) (53), the prior publication demonstrated that 25 and 21% of EDEN survivors had cognitive impairment at 6 and 12 months, respectively, compared with 36 and 25% in this study that used a more sensitive and comprehensive battery of performancebased cognitive tests. Similarly, initial trophic feeding versus full enteral feeding did not affect any of the patient-reported outcomes (2).…”
Section: Discussionmentioning
confidence: 99%
“…The MMSE has many well-known benefits, particularly its rapid application and high sensitivity and specificity in relation to cognitive dysfunctions . Moreover, the values reported in several psychometric studies have shown the MMSE to be a perfectly valid and reliable test (Ferrell et al 2000;Newkirk et al 2004;Woodbury and Fillenbaum 1996).…”
Section: Introductionmentioning
confidence: 98%
“…Expressions of interest were sought from potential participants recruited via local advertisements, media releases and organisations for older people. Participants who met the initial inclusion criteria were screened for dementia using a modified telephone version of the Mini-Mental State Examination (52) and written informed consent was obtained. Four assessment sessions (baseline, 6, 12 and 18 months) were conducted, during which fasted blood samples were collected for determining the fatty acid profile (each assessment) as well as plasma homocysteine, serum folate and serum vitamin B 12 levels (first and final assessments).…”
Section: Methodsmentioning
confidence: 99%